THE EFFECT OF MODERNIZATION OF TAX ADMINISTRATION SYSTEM AND TAX KNOWLEDGE ON TAXPAYER COMPLIANCE - Ana Mardiana; Lukman Lukman; Anthony Holly (Universitas Katolik Indonesia Atma Jaya, 2022)
This research aims to determine (1) the influence of the modernization tax administration system on taxpayer compliance in the KPP Pratama Makassar Utara, (2) the influence of tax knowledge on taxpayer compliance in the KPP Pratama Makassar Utara. The research data obtained from the questionnaire (primary) were distributed to the taxpayer in the KPP Pratama Makassar Utara. The sample was determined by using purposive sampling with a sample size of 97 respondents. Further data have been obtained, tested by using multiple linear regression analysis. The results of the hypothesis test prove that e-SPT impacts the positive of taxpayer compliance, which means the higher the implementation of e-SPT, the higher the taxpayer compliance. E-Faktur impact on the positive of the taxpayer compliance, which means the higher the implementation of e-faktur, the higher the taxpayer compliance and tax knowledge impact on positive of the taxpayer compliance which means the higher the tax knowledge the higher the taxpayer compliance